Influence of prebiotics in pigs nutrition on body weight and content of Escherichia coli in feces - Delić-Jović Mirjana (Institute for Animal Husbandry, Belgrade, 2021)
The aim of this study was to determine the effect of prebiotics in the diet of piglets after weaning on the increase in the average weight of experimental animals between female (♀) and male (♂) piglets, dynamically by weeks of experiment, as well as on the presence of Escherichia coli in feces. The experiment included piglets at weaning, aged about 26 days. The F1 generation was used, which was created by crossing Landrace sows and Pietren boars. The piglets were fed for 56 days (8 weeks). Four groups were formed, each group was composed of 10 piglets (5 females and 5 males) with different concentrations of prebiotics and controls, in two replicates, a total of 100 experimental animals. Feed mixtures consisting of the same nutrients were used in the diet. Control groups (OA and OB) were fed with ordinary feed mixture, without the addition of additives, groups (IA and IB) with the addition of Bio-Mos prebiotics, in a concentration of 0.1%, groups (II-A and II-B) with 0.2%, groups (III-A and III-B) with 0.3% and groups (IV-A and IV-B) were fed with the addition of prebiotics in a concentration of 0.4%. It was concluded that the differences observed in the average weight between ♀ and ♂ piglets in any measurement period were not statistically significant. However, the best results in terms of average weight were given by the highest used concentrations of prebiotics in food, 0.4% and 0.3%. The preparation had a positive effect in terms of reducing the number of Escherichia coli bacteria in the digestive tract of piglets in all treatment groups by 42 to 320 times.